Evaluation of quality of life and function at 1 year after transanal endoscopic microsurgery. (February 2015) - Hompes, R.; Ashraf, S. Q.; Gosselink, M. P.; van Dongen, K. W.; Mortensen, N. J.; Lindsey, I.; Cunningham, C.
Abstract Aim Transanal endoscopic microsurgery (TEM) enables organ preservation after rectal tumour surgery. Its application is being expanded using adjuvant and neoadjuvant treatments. Our objective was to evaluate the changes over time in anorectal function, urinary symptoms and quality of life (QoL) in patients who had TEM surgery for a rectal tumour. Method Between September 2009 and October 2012, a consecutive series of 102 patients underwent TEM at a single institution. Patients were asked to fill out standardized questionnaires at baseline and then at 6, 12, 26 and 52 weeks after surgery. The QoL among these patients was assessed using one generic (EQ‐5D) and two disease‐specific [European Organization for Research and Treatment of Cancer (EORTC) QLQ‐C30 and QLQ‐CR29] questionnaires. Anorectal and urinary symptoms were studied using the COlo‐REctal Functional Outcome (COREFO) and the International Prostate Symptom Score (I‐PSS) questionnaires, respectively. Results The response rate was 90% (92/102 patients). Postoperative complications occurred in 14% (13/92) of patients. The general QoL (as assessed using the EQ‐5D) was lower 6 and 12 weeks after TEM compared with baseline QoL (P < 0.05) but returned towards baseline after 26 weeks. Anorectal function (determined using the COREFO) was worse 6 weeks postoperatively (P < 0.01) but had normalized by 12 weeks. Urinary function (determined using the I‐PSS) was not affected at any time point after surgery. The total COREFO score and the American Society of Anesthesiologists (ASA) score were correlated with the deterioration in QoL. Conclusion The study demonstrates that TEM has a temporary and reversible impact on QoL and anorectal function. Intensive interrogation of QoL and function using appropriate questionnaires will help to define the role of organ‐preserving surgery for rectal cancer before and after chemoradiotherapy.